Nonstructural carbohydrate content in the stubble per unit area regulates grain yield of the second crop in rice ratooning - Nakano, Hiroshi; Tanaka, Ryo; Hakata, Makoto (Crop science, 2022)
Rice (Oryza sativa L.) ratooning has attracted attention due to its higher yield potential. In the present study, a field experiment on rice ratooning using two rice genotypes, near isogenic line (NIL)‐GN1ATakanari and Koshihikari, was conducted in 2019 and 2020 in southwestern Japan to obtain direct evidence for the role of stubble nonstructural carbohydrate (NSC) concentration and/or content per unit area on grain yield of the second crop and to determine the effectiveness of a gene producing more spikelets. NIL‐GN1ATakanari is a near isogenic line carrying an allele of GN1A, which is a gene regulating the number of spikelets per unit area derived from an indica cultivar Takanari in the genetic background of a japonica cultivar Koshihikari, and it can produce more spikelets than Koshihikari. NIL‐GN1ATakanari did not produce a higher grain yield of the first crop than Koshihikari in both years because NIL‐GN1ATakanari had more spikelets m−2 but fewer filled spikelets and a lower grain weight. NIL‐GN1ATakanari produced a lower grain yield of the second crop than Koshihikari because NIL‐GN1ATakanari had fewer spikelets m−2 due to the fewer panicles. Also, NIL‐GN1ATakanari had a lower NSC content than Koshihikari due to the lower leaf sheath plus stem weight in the stubble in 2019. Thus, the lower grain yield in the second crop of NIL‐GN1ATakanari may result from the lower NSC content in the stubble. Additionally, the ability to produce more spikelets per unit area of NIL‐GN1ATakanari was not demonstrated in ratoon crop under the condition of low NSC content in the stubble. Core Ideas NIL‐GN1ATakanari produced a lower grain yield of the second crop than Koshihikari. NIL‐GN1ATakanari had fewer spikelets m−2 of the second crop than Koshihikari. NIL‐GN1ATakanari had a lower NSC content in the stubble than Koshihikari. The lower grain yield of NIL‐GN1ATakanari may result from the lower NSC content in the stubble.